2008
DOI: 10.1111/j.1553-2712.2008.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated Cocktails: Energy Drink Consumption, High‐risk Drinking, and Alcohol‐related Consequences among College Students

Abstract: Objectives: The consumption of alcohol mixed with energy drinks (AmED) is popular on college campuses in the United States. Limited research suggests that energy drink consumption lessens subjective intoxication in persons who also have consumed alcohol. This study examines the relationship between energy drink use, high-risk drinking behavior, and alcohol-related consequences. Methods:In Fall 2006, a Web-based survey was conducted in a stratified random sample of 4,271 college students from 10 universities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
536
8
21

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 432 publications
(606 citation statements)
references
References 24 publications
41
536
8
21
Order By: Relevance
“…It may also be that co-consumption of alcohol with EDs reduce hangover effects, making alcohol use less subjectively problematic. Use to reduce hangover symptoms is flagged by a significant minority of consumers (O'Brien et al, 2008), although these studies have typically focused on university students, with few experimental studies exploring this possible phenomenon (Rohsenow et al, 2014). Regardless, frequency of ED use could serve as flag in clinical settings for potential hazardous alcohol use, important given possible stigma associated with reporting problematic alcohol use (Fortney et al, 2004).…”
Section: Wellbeingmentioning
confidence: 99%
“…It may also be that co-consumption of alcohol with EDs reduce hangover effects, making alcohol use less subjectively problematic. Use to reduce hangover symptoms is flagged by a significant minority of consumers (O'Brien et al, 2008), although these studies have typically focused on university students, with few experimental studies exploring this possible phenomenon (Rohsenow et al, 2014). Regardless, frequency of ED use could serve as flag in clinical settings for potential hazardous alcohol use, important given possible stigma associated with reporting problematic alcohol use (Fortney et al, 2004).…”
Section: Wellbeingmentioning
confidence: 99%
“…15 Even after adjusting for the increased alcohol consumed, college students who drank CaffAlc beverages reported significantly higher prevalence of serious alcohol-related consequences, including alcohol-related illness or injury, sexual assault, and riding with a drunken driver. 14 Several mechanisms have been suggested to explain the observed association between CaffAlc, risky drinking, and alcohol-related harms. Drinkers who believe that caffeine neutralizes the depressive effects of alcohol may expect that by consuming CaffAlc, they can safely tolerate greater quantities of alcohol without impairment.…”
Section: Introductionmentioning
confidence: 99%
“…13 The consumption of caffeinated alcohol (CaffAlc) has been found to be significantly associated with increased frequency of high-risk drinking behaviors in college students, including heavy episodic drinking and weekly drunkenness. 14 A study of patrons exiting a U.S. college bar district found individuals who consumed CaffAlc to be three times more likely to be legally intoxicated than individuals who consumed alcohol alone, 15 and four times more likely to report intention of driving, compared to patrons who consumed only alcohol. 15 Even after adjusting for the increased alcohol consumed, college students who drank CaffAlc beverages reported significantly higher prevalence of serious alcohol-related consequences, including alcohol-related illness or injury, sexual assault, and riding with a drunken driver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] A growing body of research has found AmED use to be associated with significantly more risky behavioral outcomes than noncaffeinated alcohol use alone. O'Brien et al 23 found that college student AmED users reported more drinks per typical occasion, twice as much drunkenness and binge drinking, and more alcohol-related unwanted outcomes than those who drank alcohol alone; they were more likely to take advantage of someone or be taken advantage of sexually, ride with a drunk driver, be hurt or injured, require medical treatment, and (for moderate drinkers) drive while intoxicated. These findings were largely replicated by Brache and Stockwell 20 in a Web survey of Canadian students, for whom frequent AmED use was associated with more frequent drinking and with higher odds of heavy episodic drinking, drinking and driving, or being hurt or injured.…”
mentioning
confidence: 99%